Ha ketten csinálják ugyanazt, nem ugyanaz – a segítés női és férfi mintázatai - HÉZSER, Gábor; KRASZNAY , Mónika (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
If Two Do the Same Thing, It Is Not the Same Thing – Male and Female Patterns of Helping It is assumed that a professional’ gender has a decisive influence on the need for help, the way of providing help, and the helping relationship. Our aim is to sensitize pastoral care workers and other helping professionals to this perception and conscious recognition. In connection with our topic, we will make some points that we recommend to be mindful of. We will take into account what the theory of science points out: in the studies and theses of the social sciences and humanities, the researcher and the object of research are “structurally identical”. We will discuss the deforming effects of masculine dominance and some of its implications for the history of science, theology, and the practice theory of helping. Then we discuss the reality of the correlative determination of identity. We will point out that the far-reaching disregard of feminine and masculine patterns of helping is not unique to pastoral care. A similar omission can be observed in the fields of medicine and psychotherapy training. Finally, attention is drawn to practical aspects relevant to pastoral care.